Physical properties of the type-I clathrate phase Ba8−xEuxAuySi46−y. (1st May 2017) - Tomeš, P.; Himmelbauer, T.; Sidorenko, A.; Yan, X.; Prokofiev, A.; Paschen, S.
Abstract: The effect of the substitution of rare–earth atoms for guest atoms on the low-temperature transport and magnetic properties is investigated for single-crystalline type–I clathrates with the nominal composition Ba8− x Eu x Au y Si46− y ( x  = 1.0, 1.68 and y  = 4.77, 5.32). The Seebeck coefficient and Hall coefficient data show that a transition from n - to p -type conduction takes place with increasing Au content. The n -type sample presents a large maximum in the thermal conductivity due to the freezing of three phonon Umklapp scattering processes at low temperatures, whereas the maximum of thermal conductivity in the p -type sample is strongly reduced due to dominant phonon-electron scattering process. Both samples are metal–like and ferromagnetic, with Curie temperatures TC of 3.1 K and 10.0 K for x  = 1.0 and 1.68, respectively. The magnetization measurement confirmed the Eu 2+ state in both samples and the Ruderman-Kittel-Kasuya-Yoshida (RKKY) interaction model explains the FM-type of order in which the nearest-neighbor (NNN) and the next-nearest-neighbor (NN) interactions play a major role at x  = 1.0 and 1.68, respectively. Graphical abstract: Image 1